PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT PENDERITA GOUT ARTRITIS - Malensang, Ester Lita; Rakinaung, Natalia Elisa; Oroh, Cindi T M (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2024)
Introduction: Purine metabolism disorders in the body can cause gout arthritis which is characterized by hyperuricemia. People with gout arthritis can experience limited activity, be less productive at work, thus affecting economic income If this condition is not treated, sufferers can develop feelings of helplessness and hopelessness, to the point of becoming indifferent to their health. One way to treat gout arthritis is by taking medication when the disease recurs. Therefore, it is necessary to study further regarding the knowledge factors of gout arthritis sufferers and family support in efforts to take medication obediently. Objective: To analyze the knowledge factors and family support with medication adherence in gout arthritis sufferers. Method: This study is a quantitative study with a cross-sectional approach. This study was conducted in the Tule Health Center work area, with a population size of 80 people suffering from arthritis and a sample size of 80 people (total sampling). The instruments used were a knowledge questionnaire, family support questionnaire, and medication adherence questionnaire. Results: The results of the Chi Square test, found a p-value of 0.000 <0.05, meaning that there is a relationship between knowledge and medication adherence, there is also a relationship between family support and medication adherence, where the p-value is 0.042 <0.05. Conclusions: Knowledge of gouty arthritis sufferers and family support have a relationship with medication adherence in gouty arthritis sufferers.